USING PHILOSOPHICAL HERMENEUTICS IN IMPROVING COMMUNICATION ETHICS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article examines the problems of communication ethics that arise in the oral and alternative approaches to communication in hermeneutic studies dealing with the theory of interpretation of philosophy. As a result, this topic is also relevant because it helps to develop methods for the scientific and philosophical classification and theoretical improvement of the ethical aspects of communication.